Protecting healthcare workers against coronavirus disease 2019 in emergency departments at a teaching hospital in Tabriz, Iran: a best practice implementation project. Issue 3 (10th September 2022) - Talebpour, Amin; Hajebrahimi, Sakineh; Tavani, Fatemeh Molaei; Rahmani, Parvin; Ghabousian, Amir; Kabiri, Neda
ABSTRACT: Introduction: The first case of the novel coronavirus disease (COVID-19) in Iran was officially announced on February 19, 2020, in Qom city. The prevalence of COVID-19 is higher among frontline healthcare workers (HCWs) due to their occupational exposure. Objective: The aim of this evidence implementation project was to improve the protection of nurses against COVID-19 in the emergency department of a teaching hospital in Tabriz, Iran. Methods: A clinical audit was undertaken using the JBI Practical Application of Clinical Evidence System (JBI PACES) tool. Ten audit criteria, representing the best practice recommendations for the protection of HCWs in the emergency department were used. A baseline audit was conducted, followed by the implementation of multiple strategies. The project was finalized with a follow-up audit to evaluate changes in practice. Results: The baseline audit results showed that the compliances for four (out of ten) audit criteria (criteria 4, 7, 8 and 9), were under 75%, which indicated poor and moderate compliance with the current evidence. After implementing plans such as running educational programs and meetings, major improvement was observed in 3 criteria, criterion 4 was improved from low to excellent (41–81%), criterion 7 was promoted from low to moderate (30–62%), criterion 8 was not promoted considerably (22–27%) and criterion 9 was improved from moderate to excellent (70–84%). Conclusion: The results of the audit process increased COVID-19 protection measures for nurses in the emergency department. It can be concluded that educational programs and tools, such as face-to-face training, educational pamphlets, workshops and meetings can facilitate the implementation of evidence into practice.